FSH, oxytocin and IGF-I regulate the expression of sirtuin 1 in porcine ovarian granulosa cells - Sirotkin, A V; Dekanová, P; Harrath, A H (Physiological research, 2020)
The involvement of the mTOR system/enzyme sirtuin 1 (SIRT1) intracellular signaling system in the control of ovarian functions and its role in mediating hormonal action on the ovary has been proposed, but this hypothesis should be supported by a demonstrated influence of hormones on mTOR/SIRT1. Therefore, the aim of our in vitro experiments was to examine the effect of the known hormonal regulators of ovarian functions, such as follicle-stimulating hormone (FSH), oxytocin (OT) and insulin-like growth factor I (IGF-I), on mTOR/SIRT1. The accumulation of SIRT1 in porcine ovarian granulosa cells cultured with and without these hormones (at doses of 1, 10 or 100 ng.ml-1) was evaluated using immunocytochemistry. It was observed that the addition of FSH (at 10 ng.ml-1 but not at 1 or 100 ng/ml) and OT (at all tested doses) increased the expression of SIRT1 in ovarian cells. In addition, 100 ng.ml-1, but not at 1 or 10 ng.ml-1, of IGF-I decreased SIRT1 accumulation. Our observations are the first demonstration that hormones can directly regulate the ovarian mTOR/SIRT1 system and that this system could mediate the action of hormonal regulators on the ovary.
Keywords: Granulosa Cells; Sirtuin 1; Oxytocin; oxytocin; Insulin-Like Growth Factor I; Female; Follicle Stimulating Hormone; folikuly stimulující hormon; insulinu podobný růstový faktor I; Cells, Cultured; zvířata; proliferace buněk; apoptóza; Oxytocics; Swine; folikulární buňky; ženské pohlaví; uterotonika; kultivované buňky; Cell Proliferation; prasata; ovarium; Animals; Ovary; sirtuin 1; Apoptosis